A thiol‐disulfide oxidoreductase of the Gram‐positive pathogen Corynebacterium diphtheriae is essential for viability, pilus assembly, toxin production and virulence. Issue 6 (25th September 2015) - Reardon‐Robinson, Melissa E.; Osipiuk, Jerzy; Jooya, Neda; Chang, Chungyu; Joachimiak, Andrzej; Das, Asis; Ton‐That, Hung
Summary: The Gram‐positive pathogen C orynebacterium diphtheriae exports through the Sec apparatus many extracellular proteins that include the key virulence factors diphtheria toxin and the adhesive pili. How these proteins attain their native conformations after translocation as unfolded precursors remains elusive. The fact that the majority of these exported proteins contain multiple cysteine residues and that several membrane‐bound oxidoreductases are encoded in the corynebacterial genome suggests the existence of an oxidative protein‐folding pathway in this organism. Here we show that the shaft pilin SpaA harbors a disulfide bond in vivo and alanine substitution of these cysteines abrogates SpaA polymerization and leads to the secretion of degraded SpaA peptides. We then identified a thiol‐disulfide oxidoreductase (MdbA), whose structure exhibits a conserved thioredoxin‐like domain with a CPHC active site. Remarkably, deletion of mdb A results in a severe temperature‐sensitive cell division phenotype. This mutant also fails to assemble pilus structures and is greatly defective in toxin production. Consistent with these defects, the Δ mdbA mutant is attenuated in a guinea pig model of diphtheritic toxemia. Given its diverse cellular functions in cell division, pilus assembly and toxin production, we propose that MdbA is a component of the general oxidative folding machine in C . diphtheriae . Abstract : Folding of unfolded protein precursors transported by the Sec apparatus is not fully explored in Gram‐positive bacteria. We show here the membrane‐bound thiol‐disulfide oxidoreductase MdbA catalyzes post‐translocational protein folding in the actinobacterial pathogen Corynebacterium diphtheriae . Significantly, the mdbA mutant is defective in growth and attenuated in virulence, making C. diphtheriae an excellent model to study therapeutics targeting disulfide bond formation in important Actinobacterial pathogens like mycobacteria.